Estimativa do módulo de elasticidade transversal para madeiras de espécies nativas via ensaios de flexão estática - Aguiar, Fabricio da Silva (2024)
Wood has been playing a key role in civil construction due to its structural and, especially, sustainable properties. The transverse elasticity modulus (G) is an important elastic property for the proper analysis and dimensioning of structural components. However, its determination for native wood species in Brazil lacks a standardized experimental test. Faced with this gap, this study addresses the estimation of the shear modulus (G) for tropical woods through static bending tests. For this purpose, the influence of deformations due to shear forces on the deflection of beam elements was investigated, as well as the comparison of using static bending tests at three and four points in estimating the longitudinal and transverse elasticity modulus. Six different native species were employed in the study: Pequiá (Caryocar villosum), Marupá (Simarouba amara), Cupiúba (Goupia glabra), Sapucaia (Lecythis spp.), Tatajuba (Bagassa guianensis), and Roxinho (Peltogyne spp.), and the tests were conducted according to three standards (ABNT NBR 7190-3:2022, ISO/FDIS 13910:2014, and BS EN 408:2010). The results showed that for the ratio between span and cross-sectional height equal to or less than 18, deformations due to shearing significantly influence the calculation of the longitudinal elasticity modulus (E). Furthermore, the three-point static bending test proved more suitable for estimating G. The ratio between longitudinal and transverse elasticity modulus varied from G=E/5 to G=E/18, diverging from the Brazilian standard results.